The Stabilization Effects of Fiscal Policy on Banking System Stability in Nigeria - AMADI, Agatha Nkem; ADETILOYE, Kehinde Adekunle; OMANKHANLEN, Alexander Ehimare; AMADI, Idimmachi Pius; NWODIMMAH, Pascal (Asian Economic and Financial Review, 2021)
This study examined the stabilization effect of fiscal policy on banking system stability in Nigeria using data from 1985 to 2019. The study adopted the ordinary least squares, cointegration and error correction techniques to analyze and determine the existence of a long-run relationship among the variables. The ordinary least squares technique was used to evaluate the impact of the interaction between fiscal policy and banking system stability variables. The findings indicate that fiscal policy has a strong influence on banking system stability in Nigeria. It was further discovered that, among the fiscal policy variables, taxation and government debt have a more positive effect on banking systems than other variables used in the study, while government funding and debt growth have a negative effect on banking system stability. This indicates that the more debt the government accumulates, the greater the instability of the banking system. The study recommends that the government put appropriate controls in place to avoid borrowing that will creep into deficit, which will, in turn, affect the banking system stability. The government should also ensure that its borrowings are channeled into productive segments of the economy to enhance the sustainable repayment of debt and ensure that the mechanisms for debt repayment are strictly adhered to.